Quantitative analysis of extra-computer room monitoring services to auxiliate students in their school practices - Santos, Franciélen Aparecida dos; Santos, Carlos Henrique da Silva (Revista Hipótese, 2022)
Difficulties in technical subjects and access to computing resources may require alternative educational practices, such as student-monitor institutionalization. In this context, this work analyzes the impact that an instructional monitoring action was taken in the IFSP, Itapetininga campus, and how this contributed to the extra-room attendance and the creation of a culture of students stay in the counterpart, potentializing their exchanges of knowledge and experience.